2020
DOI: 10.1111/and.13558
|View full text |Cite
|
Sign up to set email alerts
|

Oral dapoxetine versus topical lidocaine as on‐demand treatment for lifelong premature ejaculation: A randomised controlled trial

Abstract: This trial aimed to assess the efficacy of on‐demand oral dapoxetine versus topical lidocaine treatments for lifelong PE. Cases with lifelong PE were randomised to start treatment by oral dapoxetine 60 mg or topical lidocaine 10% spray. The intravaginal ejaculatory latency time (ILET), validated Arabic Index for PE (AIPE), Sexual Health Inventory for Men (SHIM) and frequency of intercourse/week were recorded at the baseline and after 12 weeks treatment period of the first medication before two weeks washout pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In their study, Alghobary et al reported a decrease in erection that did not interfere with intercourse in 61.8% of patients treated with topical lidocaine, while glans penile irritation was reported in 4 patients (7.3%). 11 In a study using Fortaci, an aerosol containing 150 mg/mL lidocaine and 50 mg/mL prilocaine, they observed side effects such as genital burning sensation (7.0%), bothersome local hypoesthesia (3.9%) and erectile dysfunction (2.3%). 17 In the study conducted by Dell'Atti et al, genital burning sensation was detected in 4%, genital erythema in 4%, and hypoesthesia in the penis in 8% of the group using topical lidocaine spray 10%.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, Alghobary et al reported a decrease in erection that did not interfere with intercourse in 61.8% of patients treated with topical lidocaine, while glans penile irritation was reported in 4 patients (7.3%). 11 In a study using Fortaci, an aerosol containing 150 mg/mL lidocaine and 50 mg/mL prilocaine, they observed side effects such as genital burning sensation (7.0%), bothersome local hypoesthesia (3.9%) and erectile dysfunction (2.3%). 17 In the study conducted by Dell'Atti et al, genital burning sensation was detected in 4%, genital erythema in 4%, and hypoesthesia in the penis in 8% of the group using topical lidocaine spray 10%.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, dapoxetine is a short-acting SSRI that increases 5-HT levels in the synaptic cleft for a short period of time and delay ejaculation. However, side effects such as diarrhoea, nausea and dizziness are inevitable (Alghobary et al, 2020). These adverse reactions disappeared quickly after patients stopped taking the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were evaluated using the Arabic Index for PE (AIPE) and the Sexual Health Inventory for Men (SHIM) questionnaire. Authors showed that both medications significantly increased both IELT and AIPE scores when compared with baseline evaluation, but the results were shown to be significantly better with topical lidocaine with respect to oral dapoxetine [28].…”
Section: Lidocaine-only Spraymentioning
confidence: 99%
“…However, these preparations carry the risks of sensibility reduction for both patients and their partners, which may potentially lead to erectile dysfunction and skin irritation [27]. Additionally, cream preparations for PE are used on-demand, which could result in loss of spontaneity and subsequent loss of sexual arousal [28] causing treatment discontinuation and poor patient's compliance.…”
Section: Cream Formulationsmentioning
confidence: 99%